Предмет: Алгебра,
автор: djdygbh3563
розв'яжіть рівняння (х2-2х)^2+2(х2-2х)-3=0
Ответы
Автор ответа:
1
Відповідь: х = 1 .
Пояснення:
(х²-2х)² + 2(х²-2х) - 3 = 0 ;
вводимо нову змінну : z = х²- 2х ;
z² + 2z - 3 = 0 ; D = 4 + 12 = 16 > 0 ; z₁ = - 3 ; z₂ = 1 .
Повернемося до змінної х :
х² - 2х = - 3 ; або х² - 2х = 1 ;
х² - 2х + 3 = 0 ; х² - 2х + 1 = 0 ;
D = 4 - 12 = - 8 < 0 ; ( x - 1 )² = 0 ;
x₁Є ∅ ; х - 1 = 0 ;
x₂ = 1 .
В - дь : х = 1 .
djdygbh3563:
спасибо)
Похожие вопросы
Предмет: Українська мова,
автор: nikitacuba673
Предмет: Английский язык,
автор: juliaglita11
Предмет: Математика,
автор: danielamizraki
Предмет: История,
автор: steammy546
Предмет: Биология,
автор: bodnaaar